Why Not Indonesia an Islamic State? Constitutional Debate Concerning Religion-State Relation in A Muslim Majority Country - Omara, Andy (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
When Muslims are majority in a particular country, it is often linked to the adoption of Islam as the state official religion or Islam as the identity of the state i.e. “Islamic State.” Yet, this is not the case of Indonesia. Why did not the Indonesian constitutional drafters declare Indonesia as an Islamic state or at least recognize Islam as the state official religion in the first Constitution despite the fact that Indonesia is a Muslim majority country? What explains the above fact? This paper aims to answer these two important questions by employing two constitutional law approaches: constitutional history and constitutional deferral. Constitutional history aims to understand the original intentions of the framers of the first Constitution through studying the minutes of the 1st Constitution. Constitutional deferral concept is used to explain the formulation of state-religion relation in the provisions of the first Constitution. This paper argues the fact that the constitutional drafters did not expressly state Islam as the state official religion in the Constitution did not mean that they overlooked to discuss such an important topic, rather because they had diverse views on how to include religion-state relation in the constitution. The sharp ideological difference among constitutional drafters is likely the cause of the adoption of constitutional deferral -a method of drafting constitutional through somewhat general and abstract provisions. The use of constitutional deferral is favorable because it opens more opportunity among constitutional drafters to achieve consensus and get things done. In practice, Indonesia is not a country officially based on Islam, but substantially Islamic values live in Indonesia. This article contributes to the study of the relationship between state and religion in Indonesia, regarding the current and future background and dialectics.